2012
DOI: 10.1089/jpm.2011.0178
|View full text |Cite
|
Sign up to set email alerts
|

The POLST Program: A Retrospective Review of the Demographics of Use and Outcomes in One Community Where Advance Directives Are Prevalent

Abstract: Objectives: Determine the use and utility of the Physician Orders for Life-Sustaining Treatment (POLST) program in a community where powers of attorney for health care (POAHCs) are prevalent. Methods: A retrospective review of medical record and death certificate data of 400 adults who died between September 1, 2007, and March 31, 2008, in the La Crosse County, Wisconsin community. Demographic and cause-of-death data were collected from death certificates. Information about POAHC, POLST forms, and medical trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(104 citation statements)
references
References 7 publications
3
99
0
2
Order By: Relevance
“…This program has led to a regional prevalence of 90% of patients having advance directives and 99% of those advance directives being available on admission to the hospital (42). More than two-thirds of patients have physician orders for life-sustaining treatment (POLST) on admission to the hospital to guide the admitting health care team about limitations to care (43). Whether these results can be accomplished in a more heterogeneous and/or disadvantaged population with less trust in the health care system has not been tested.…”
Section: Models That Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This program has led to a regional prevalence of 90% of patients having advance directives and 99% of those advance directives being available on admission to the hospital (42). More than two-thirds of patients have physician orders for life-sustaining treatment (POLST) on admission to the hospital to guide the admitting health care team about limitations to care (43). Whether these results can be accomplished in a more heterogeneous and/or disadvantaged population with less trust in the health care system has not been tested.…”
Section: Models That Workmentioning
confidence: 99%
“…Psychoeducational sessions conducted by advanced practice nurses for patients with advanced cancer in the Project ENABLE study improved patients' quality of life and mood, although the sessions did not have an impact on symptom intensity or visits to the hospital, ICU, or emergency department. Studies of the use of palliative care in family medicine and pulmonology include the previously described outpatient and inpatient consultative approaches in San Francisco (41)(42)(43), as well as a study from Australia showing that case conferences bringing together general practitioners and specialist palliative care teams may improve some aspects of patient quality of life (65). Gade et al (34) found improvement in care for hospitalized patients with life-limiting illnesses using an interdisciplinary palliative care service and internal medicine (19,34).…”
Section: Medical Specialties Where Palliative Care Is and Needs To Bementioning
confidence: 99%
“…8 POLST offers advantages over traditional code status orders by permitting documentation of a wide range of treatment preferences including resuscitation, medical interventions such as hospitalization, antibiotics, and artificial nutrition. [9][10][11][12][13] It is recommended that the POLST be generated before hospital discharge for eligible patients 14 to help ensure that patients have orders available during transport and upon arrival at the facility or home. When patients lack decisional capacity and there are no orders available reflecting prior treatment decisions, the default is to provide all available medical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…8 Our outcomes complement other reports of the power of a systematic and comprehensive approach to advance care planning prior to the end of life for dialysis patients with CFTT. 9 Advance care planning, completion of POST, and guided withdrawal processes allow deliberate determinations about the end of life, are associated with greater hospice utilization, and may facilitate the chance for an out-of-hospital death. a Decision made by both the patient and family in 4 cases and solely by the family in 11 cases; two patients with decision making capacity despite mild cognitive impairment refused further treatment.…”
Section: Discussionmentioning
confidence: 99%